Improving Health and Reducing Comorbidity Associated with HIV: The Development of TAVIE en santé, a Web-Based Tailored Intervention to Support the Adoption of Health Promoting Behaviors among People Living with HIV. (14th March 2017) - Côté, José; Cossette, Sylvie; Ramirez-Garcia, Pilar; Rouleau, Geneviève; Auger, Patricia; Boudreau, François; Gagnon, Marie-Pierre
Abstract : Background . In the domain of health behavior change, the deployment and utilization of information and communications technologies as a way to deliver interventions appear to be promising. This article describes the development of a web-based tailored intervention, TAVIE en santé, to support people living with HIV in the adoption of healthy behaviors. Methods . This intervention was developed through an Intervention Mapping (IM) framework and is based on the theory of planned behavior. Results . Crucial steps of IM are the selection of key determinants of behavior and the selection of useful theory-based intervention methods to change the targeted determinants (active ingredients). The content and the sequence of the intervention are then created based on these parameters. TAVIE en santé is composed of 7 interactive web sessions hosted by a virtual nurse. It aims to develop and strengthen skills required for behavior change. Based on an algorithm using individual cognitive data (attitude, perceived behavioral control, and intention), the number of sessions, theory-based intervention methods, and messages contents are tailored to each user. Conclusion . TAVIE en santé is currently being evaluated. The use of IM allows developing intervention with a systematic approach based on theory, empirical evidence, and clinical and experiential knowledge.